CONSTANS Polymorphism Modulates Flowering Time and Maturity in Soybean - Awal Khan, Mohammad Abdul; Zhang, Shouwei; Emon, Reza Mohammad; Chen, Fulu; Song, Wenwen; Wu, Tingting; Yuan, Shan; Wu, Cunxiang; Hou, Wensheng; Sun, Shi; Fu, Yongfu; Jiang, Bingjun; et al. (Frontiers in Plant Science, 2022)
CONSTANS (CO) plays a critical role in the photoperiodic flowering pathway. However, the function of soybean CO orthologues and the molecular mechanisms in regulating flowering remain largely unknown. This study characterized the natural variations in CO family genes and their association with flowering time and maturity in soybeans. Twenty-one soybean CO family genes (GmCOLs) were cloned and sequenced in 128 varieties covering 14 known maturity groups (MG 0000-MG X from earliest to latest maturity). Regarding the whole genomic region involving these genes, GmCOL1, GmCOL3, GmCOL8, GmCOL9, GmCOL10 and GmCOL13 were conserved, and the remaining 15 genes showed genetic variation that was brought about by mutation, viz. all SNPs and InDels. In addition, a few genes showed some strong linkage disequilibrium. Fifteen GmCOL genes showed point mutations, which can lead to changes in the potential protein structure. Eight genes (GmCOL1/3/4/8/13/15/16/19) were related to early flowering and maturation. Eleven genes (GmCOL2/5/6/14/20/22/23/24/25/26/28) expressed divergent physiognomy for flowering and maturation. Haplotype analysis indicated that the haplotypes of GmCOL5-Hap2, GmCOL13-Hap2/3 and GmCOL28-Hap2 were associated with flowering dates and soybean maturity. This research will help to address the role of GmCOL family genes in adapting to diverse environments, particularly when it is necessary to regulate soybean flowering dates and maturity.